CONTEMPORARY DIAGNOSIS OF CORONARY MICROVASCULAR DYSFUNCTION IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION - Milašinović, Dejan; Stanković, Goran (Medicinski podmladak, 2024)
Coronary microvascular dysfunction (CMD) is encountered in up to 50% of patients presenting with ST-segment elevation acute myocardial infarction (STEMI) and treated with primary percutaneous coronary intervention (PCI). The current reference standard to diagnose microvascular injury in this setting is cardiac magnetic resonance (CMR) imaging. The extent of microvascular injury, termed microvascular obstruction (MVO) on CMR, increases over time after recanalization of the infarct-related artery (IRA), until it reaches its peak around day 3, and it subsides by day 10. Most of the current research evaluated MVO on CMR on days 2-7 after primary PCI, and showed its association with cardiac death and heart failure independently of the infarct size. As microvascular injury becomes a new therapeutic target in STEMI, given the plateauing mortality curves despite widespread access to timely reperfusion, the question of early diagnosis of CMD grows in importance. To this end, invasive coronary microcirculation assessment in the recanalized IRA immediately after primary PCI, has been tested in terms of its association with MVO and infarct size on CMR, as well as its ability to predict adverse clinical outcomes. Both invasive thermodilution- and Doppler wire-derived indices of microvascular resistance were successful in stratifying patients according to the risk of  cardiac death and heart failure in the follow-up. Recently, a coronary angiography-based method, which unlike thermodilution and Doppler derives indices of microvascular resistance from a computational dynamics software and does not require additional wiring of the epicardial artery, has demonstrated the ability to predict adverse clinical outcomes. The described diagnostic tools for stratification of patients according to the risk of CMD and consequently impaired prognosis after STEMI, still remain a subject of on-going research, in terms of both the most relevant cut offs for different indices and the optimal time point of assessment.
Keywords: coronary microcirculation; acute myocardial infarction